MODERNIZATION OF JEWELRY, ORNAMENTS, AND COSMETIC ADORNMENTS AMONG WOMEN IN THE SURKHANDARYA OASIS - Toshtemirov Shakhboz Azamatovich (American Journals Publishing, 2025)
The article analyzes the modernization of jewelry, ornaments, and cosmetic practices among women in the Surkhandarya Valley. The study highlights the traditional culture of jewelry and cosmetics, as well as their connection with social, economic, and cultural factors. It examines how the forms, styles, and meanings of jewelry and cosmetic items have changed from the early 20th century to the present, and how they developed under the influence of the Soviet era and modern cosmetology. The article explores the transformation of the material culture of women in the Surkhandarya Valley, focusing on the adaptation, integration, and modernization of traditions.
Keywords: Surkhandarya Valley, women, jewelry, ornaments, cosmetics, cosmetic practices, jewelry art, tradition, modernization.